Fiber Hemp Biomass Yield and Quality on Shallow Stony Soil in Southwest Germany - Beatrice E. Greiner; Jana Kunisch; Galina Krauße; Theresa Thiel; Klaus Schwadorf; Moritz von Cossel (Land)
Shallow arable soils (<35 cm depth) are classified as marginal for common agriculture but may still support biomass production from industrial crops like fiber hemp, which has a low indirect land-use change risk. However, little is known about hemp’s performance under such conditions. Therefore, this study investigated the biomass yield and quality of fiber hemp and other crops on a shallow (<35 cm), stony (>15% stone content), and clay-rich (>50% clay content) soil at 800 m above sea level in Southwest Germany (2018–2021). A randomized field trial tested different row widths and nitrogen (N) fertilization levels to assess low-input options for the given type of marginal land. Across years and row widths, hemp achieved average grain dry matter (DM) yields of 1.3 Mg/ha at a fertilization rate of 40 kg N/ha and 1.6 Mg/ha at 120 kg N/ha (with on average 30.9 ± 1.4% crude fat content across treatments). The average stem DM yields accounted for 5.11 Mg/ha (40 kg N/ha) and 6.08 Mg/ha (120 kg N/ha), respectively. Reduced N fertilization (40 kg/ha) lowered DM yields by up to 16% compared to full fertilization (120 kg/ha), but the effect was not significant and weaker at wider row spacing (45 cm). Additionally, maize reached acceptable DM yields (>17 Mg/ha). These findings suggest that shallow soils classified as marginal require reassessment, as they may offer viable opportunities for sustainable industrial hemp cultivation and contribute to a bio-based economy.